Sarcoidosis detected due to tattoo swellings in an Indian female - Ashok Ghorpade (Indian Journal of Pathology and Microbiology, 2015)
A female patient presented with asymptomatic swellings in old blue-black tattoo marks of her forearms. On careful skin examination, few raised erythematous, circular plaques were also found on the non-tattooed skin on her back, about which she was unaware. The diagnosis of cutaneous and systemic sarcoidosis was confirmed after classical histopathological findings from skin lesions from her non tattooed back and from papulonodular tattooed lesions, ruling out other causes of granulomas and supported by a negative Mantoux test, raised serum angiotensin converting enzyme level, high resolution computed tomography thorax, etc. She responded well to oral steroid therapy. The importance of a careful skin examination, easy access provided by skin lesions in suspected cases of cutaneous/systemic sarcoidosis, the value of sudden tattoo changes in the diagnosis here and the possible contribution of tattoos toward the causation of cutaneous and/or systemic sarcoidosis are highlighted.